Improvement in Sperm Parameters With Traditional Iranian Remedy - Farnaz Sohrabvand MD; Somaye Mahroozade MD; Sodabe Bioos MS; Seyed Mohammad Nazari MD, PhD; Fataneh Hashem Dabaghian MD (SAGE Publishing, 2017)
Introduction. Idiopathic male infertility is a global problem with almost no definite medicinal treatment. Most patients have to go through intrauterine insemination or assisted reproductive technology for achieving fertility. Unfortunately, success rates are low in cases with very low sperm count. Therefore it seems that improvement in sperm quality can have beneficial effects on assisted reproductive technology outcome. Case Report. A 39-year-old man with history of infertility for 6 years was referred to the traditional medicine clinic with a recurrent unsuccessful intracytoplasmic sperm injection trial. His sperm analysis showed severe oligoasthenoteratozoospermia. After taking a traditional remedy he had a remarkable improvement in his sperm parameters, which led to the formation of 8 embryos in the following intracytoplasmic sperm injection cycle. Conclusion. Traditional medicine presents various food and remedy options for treating male infertility. It seems that combination therapy can be beneficial in obtaining better results in treatment of male idiopathic infertility.